Thermal ablation effects on rotors that characterize functional re‐entry cardiac arrhythmia. (27th May 2022) - Dantas, Eber; Orlande, Helcio R. B.; Dulikravich, George S.
Abstract: Thermal ablation is a well‐established successful treatment for cardiac arrhythmia, but it still presents limitations that require further studies and developments. In the rotor‐driven functional re‐entry arrhythmia, tissue heterogeneity results on the generation of spiral/scroll waves and wave break dynamics that may cause dangerous sustainable fibrillation. The selection of the target region to perform thermal ablation to mitigate this type of arrhythmia is challenging, since it considerably affects the local electrophysiology dynamics. This work deals with the numerical simulation of the thermal ablation of a cardiac muscle tissue and its effects on the dynamics of rotor‐driven functional re‐entry arrhythmia. A non‐homogeneous two‐dimensional rectangular region is used in the present numerical analysis, where radiofrequency ablation is performed. The electrophysiology problem for the propagation of the action potential in the cardiac tissue is simulated with the Fenton–Karma model. Thermal damage caused to the tissue by the radiofrequency heating is modeled by the Arrhenius equation. The effects of size and position of a heterogeneous region in the original muscle tissue were first analyzed, in order to verify the possible existence of the functional re‐entry arrhythmia during the time period considered in the simulations. For each case that exhibited re‐entry arrhythmia, six different ablation procedures were analyzed, depending on the position of the radiofrequency electrode and heating time. The obtained results revealed the effects of different model parameters on the existence and possible mitigation of the functional re‐entry arrhythmia. Abstract : The figure shows how the S3 wave went around the thermally damaged region (red lines are contours of the fraction of damaged tissue) and then connected back to the top boundary. The reconnection of the wavefront to the boundary before the rotor tip was formed then reshaped the S3 wave, which continued to propagate downstream and the rotor generation was avoided by the thermally damaged region.